Executable contracts for Elixir - Bueso de Barrio, Luis Eduardo; Fredlund, Lars-Åke; Herranz, Ángel; Mariño, Julio; Benac Earle, Clara (Journal of logical and algebraic methods in programming, 2025)
This article presents the design of a library for attaching and checking executable contracts to code written in the Elixir programming language. In addition to classical contract constructs such as preconditions and postconditions, the library allows specifying exceptional behaviour (i.e., which exceptions are thrown and under which conditions), detecting non-termination issues in recursive functions by specifying a strictly decreasing order in function arguments, and associating timers with function calls to detect slow computations. The library also focuses on language-specific features, enabling the association of contracts with the reception of messages sent by processes and the attachment of constraints to variable names (useful due to variable shadowing in Elixir). Moreover, stateful contracts (i.e., with a model state) permit specifying the behaviour of stateful APIs whose operations can be linearized. Using the stateful contracts, a monitor can be employed to check that the observed state can be explained in terms of possible linearizations.